2014
DOI: 10.2174/13816128113199990516
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumoral Effect of the Non-Nucleoside DNMT Inhibitor RG108 in Human Prostate Cancer Cells

Abstract: Background: Current therapeutic strategies for advanced prostate cancer (PCa) are largely ineffective. Because aberrant DNA methylation associated with inappropriate gene-silencing is a common feature of PCa, DNA methylation inhibitors might constitute an alternative therapy. In this study we aimed to evaluate the anti-cancer properties of RG108, a novel non-nucleoside inhibitor of DNA methyltransferases (DNMT), in PCa cell lines. Methods:The anti-tumoral impact of RG108 in LNCaP, 22Rv1, DU145 and PC-3 cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 33 publications
3
29
2
2
Order By: Relevance
“…The drug displayed an EC50 of 63 μM in LNCaP and 30 μM in DU145 (Supplementary Figure 1). To investigate the effects of hydralazine on the malignant phenotype of PCa, four human PCa cell lines (LNCaP, 22Rv1, DU145, and PC-3) were exposed to two different concentrations of this drug (20 and 40 μM) or to the vehicle (PBS) during 14 days, as previously described for RG108 [11]. Cell viability was evaluated at days 0, 1, 2, 3, 7, 10, and 14.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The drug displayed an EC50 of 63 μM in LNCaP and 30 μM in DU145 (Supplementary Figure 1). To investigate the effects of hydralazine on the malignant phenotype of PCa, four human PCa cell lines (LNCaP, 22Rv1, DU145, and PC-3) were exposed to two different concentrations of this drug (20 and 40 μM) or to the vehicle (PBS) during 14 days, as previously described for RG108 [11]. Cell viability was evaluated at days 0, 1, 2, 3, 7, 10, and 14.…”
Section: Resultsmentioning
confidence: 99%
“…Specific GSTP1, APC and RARβ2 primers and TaqMan probes were designed using the Methyl Primer Express Software v1.0 (Applied Biosystems). β-actin ( ACTB ) was used as an internal reference gene to normalize for DNA input and all qMSP reactions were performed as previously described [11]. Methylation levels for each sample were derived from calibration curves constructed using serial dilutions of bisulfite modified CpGenomeTM Universal Methylated DNA (Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve nuclear transfer efficiency, several epigenetic remodeling drugs, such as the DNA methylation inhibitors AzC and RG108 have been used in efforts to ameliorate the development of cloned embryos (Ding et al, 2008). The latter, a new type of non-cytidine DNA methylation inhibitor, can markedly reduce DNA methylation in tumor cells and parthenogenetic embryos in vitro and in vivo (Graça et al, 2014;Zhang et al, 2015a). It has been demonstrated that treatment of lung adenocarcinoma cells with RG108 decreases methylation of the RASSF1A gene, inducing apoptosis (Rui and Wei, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, the existing literature regarding how DNA methylation is altered in the CNS is much more broad and well developed than literature describing drugs designed to target these mechanisms. Indeed, literature describing the use of drugs that target DNA methylation in any human pathology is essentially absent outside of developing efforts using DNMT inhibitors to slow cancer progression (101104). …”
Section: Potential Applications For Epigenetic Pharmacologymentioning
confidence: 99%